Your driver is waiting : a novel - Guns, Priya (Doubleday, 2023)
"In this spiky and hilarious 21st century reboot of the iconic film Taxi Driver, a ride share driver is barely holding it together on the hunt for love, dignity and a living wage . . . until she decides she's done waiting. Damani is tired. Her father just passed away and now she lives paycheck to paycheck in the basement of her parents' old house, caring for her mom, and driving for an app to (not even) pay the bills. Protests are all the rage--everybody's in solidarity with somebody-- and the city is roiling with them, but while she keeps hearing that they're fighting for change on behalf of people like her she's too broke to even afford to pay attention. And they're blocking the roads. That is, until she gives a ride to Jolene, and life opens up. Jolene seems like she could be the perfect girlfriend - attentive, attractive, liberal - and their chemistry is incredible. So maybe Damani can look past the one thing that's holding her back: She's never dated a white girl before. But Jolene's done the reading, she goes to every protest, and she says all the right things. Still, just as their romance intensifies, just as Damani is learning to trust, Jolene does something unforgivable, setting off an explosive chain of events. A wild ride brimming with dark comedy, piercing social commentary and propulsive writing, Your driver is waiting is a feverish take on our culture of modern alienation"--